THE EFFECT OF SERVICE INSTALLATIONS ON STRUCTURAL INTEGRITY OF SLABS IN BUILDINGS - Lwambuka, Ladislaus (Tanzania Journal of Engineering and Technology, 2017)
In building construction industry service installations, usually housed in conduit pipes, are commonly mounted inside reinforced concrete structural elements. This practice is adopted to attain aesthetical outlook at both interior and exterior surfaces of the buildings. Depending on the extent of service installations, the cross sectional area of the load bearing structural member is substantially reduced. However, the current structural design guidelines have no provision to accommodate the extent to which the existence of conduit pipes impairs the load bearing capacity of the structural element though reduced cross sectional area. This study has attempted to address this gap in structural design of buildings; it involves assessing the current design practice of considering a structural element as a full solid body and comparing its ultimate load bearing capacity with the ones containing the conduit pipes. The study findings are based on test results from laboratory experiments on reinforced concrete slab models with varying intensity of conduit pipe installations as commonly practiced on construction sites. Recommendations are put forth when and how to consider the reduced load bearing capacity through the existence of service installations as part of structural engineering designs.